Comparative analyses of the effects of divergent winds on the kinetic energy budget with the adoptions of two methods during the extratropical transition of Typhoon Rumbia (1818) - Zhou, Guanbo; Du, Jia; Cao, Jie; Liu, Lu; Li, Xingyu (Frontiers in Earth Science, 2023)
Modification of the divergent wind components and domain of interests can result in obvious changes in the kinetic energy (KE) budget of typhoons and other synoptic systems. Before analyzing the effects of divergent winds on the KE budget of Typhoon Rumbia (2018) during its entire life cycle, especially in its extratropical transition (ET) process, a hybrid integral method to partition the horizontal wind fields in a limited domain with high accuracy is adopted, in comparison with the commonly used iterative method under two sets of domains, that is, the typhoon following domain and the outermost domain that covers the entire typhoon track. The relative importance of the divergent and non-divergent winds in the KE budget is investigated in the three stages of the ET process, namely, the pre-development, re-intensification, and dissipation stages. It is found that the divergent winds computed by the iterative method with a lower accuracy result in sizable errors in spatiotemporal variations of the KE of the typhoon during its ET process, which thus leads to obvious forecasting errors.